Excessive White Matter Hyperintensity Increases Susceptibility to Poor Functional Outcomes After Acute Ischemic Stroke - Hong, Sungmin; Giese, Anne-Katrin; Schirmer, Markus D.; Bonkhoff, Anna K.; Bretzner, Martin; Rist, Pamela; Dalca, Adrian V.; Regenhardt, Robert W.; Etherton, Mark R.; Donahue, Kathleen L.; Nardin, Marco; Mocking, Steven J. T.; et al. (Frontiers in Neurology, 2021)
Objective To personalize prognostication of post-stroke outcome using MRI-detected cerebrovascular pathology, we sought to investigate the association between the excessive white matter hyperintensity (WMH) burden unaccounted for by the traditional stroke risk profile of individual patients and their long-term functional outcomes after stroke. Methods We included 890 patients who survived after acute ischemic stroke from the MRI-Genetics Interface Exploration (MRI-GENIE) study, for whom vascular risk factors (VRFs) including age, sex, atrial fibrillation, diabetes mellitus, hypertension, coronary artery disease, smoking, prior stroke history, as well as acute stroke severity, 3-to-6-month modified Ranking Scale score (mRS), WMH and brain volumes were available. We defined the unaccounted WMH (uWMH) burden via modeling of expected WMH burden based on each individual patient’s VRF profile. The association of uWMH and mRS score was analyzed by a linear regression analysis. The odds ratios of patients who achieved full functional independence (mRS<2) in between trichotomized uWMH burden groups were calculated by pair-wise comparisons. Results The expected WMH volume was estimated with respect to known VRFs. The uWMH burden was associated with long-term functional outcome (β=0.104, p<0.01). Excessive uWMH burden significantly reduced the odds of achieving full functional independence after stroke compared to the low and average uWMH burden (OR=0.4, 95% CI: [0.25, 0.63], p<0.01 and OR=0.61, 95% CI: [0.42, 0.87], p<0.01, respectively). Conclusion The excessive amount of the uWMH burden unaccounted for by the traditional VRF profile was associated with worse post-stroke functional outcomes. Further studies are needed to evaluate a lifetime brain injury reflected in WMH unrelated to patient’s VRF profile as an important factor for stroke recovery and a plausible indicator of brain health.